2019
DOI: 10.3390/ijerph16162941
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Self-Determined Motivation, Accelerometer-Determined Physical Activity, and Quality of Life in Chinese College Students

Abstract: Purpose: To better promote college students’ physical activity (PA) and quality of life (QoL), it is imperative to understand this population’s PA correlates, such as self-determined motivation and perceived competence. However, few studies existed in this area of inquiry among Chinese college students. Thus, the purpose of this study was to examine the relationships among Chinese college students’ self-determined motivation, PA, and QoL. Method: A total of 220 college students (115 females; Mage = 20.29 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 49 publications
3
40
0
2
Order By: Relevance
“…Previous studies have suggested that PA and diet are critical components of healthy lifestyle behaviors, linking not only sleep quality but also the QoL [ 6 , 7 , 8 , 9 , 10 ]. Evidence has also indicated the critical role of sleep quality in mediating the effect of PA and/or diet on maintaining good health [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that PA and diet are critical components of healthy lifestyle behaviors, linking not only sleep quality but also the QoL [ 6 , 7 , 8 , 9 , 10 ]. Evidence has also indicated the critical role of sleep quality in mediating the effect of PA and/or diet on maintaining good health [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positive psychology aims to study the developing potential and the virtue of human [2][3][4][5]. The system of human life is open and self-determined [6,7]. People have inner conflict and the ability of self-remolding.…”
Section: Introductionmentioning
confidence: 99%
“…Positive associations of quality of life in the psychological domain with physical activity were noted among Australians by Perales et al (2014), Colombians by Gomez et al (2013), Croatians by Jurakić et al (Greblo, 2010), Malaysians by Su et al (Su, 2019), and the Chinese by Tao et al (2019). Also, Wang et al (2019) in their study of working people from Shanghai found positive associations of quality of life in its psychological domain with physical activity.…”
Section: Discussionmentioning
confidence: 96%